Measurement of ivermectin concentrations in target worms and host gastrointestinal tissues: Influence of the route of administration on the activity against resistant Haemonchus contortus in lambs - Lloberas, Maria Mercedes (2012)
The influence of the administration route on the relationship between efficacy and ivermectin concentration profiles achieved in the bloodstream, the gastrointestinal mucosal tissues/fluid contents and within a target abomasal parasite (Haemonchus contortus) was evaluated in lambs. Twenty-six (26) parasitized lambs were assigned into three experimental groups: untreated (control) and ivermectin treated by the subcutaneous and intraruminal route at 0.2. mg/kg. Blood samples were collected between 0 and 15. days post-treatment (plasma disposition study). Four animals from each group were sacrificed at day 3 post-treatment. Mucosa and content samples from abomasum and small intestine and adult specimens of H. contortus were collected. Drug concentrations were measured by HPLC. Individual fecal egg counts were evaluated at -1, 3 and 15. days post treatment. Post-mortem examination was done at day 15 post-treatment. Adult nematodes recovered from the digestive tract were counted and identified by species. Ivermectin plasma availability was higher (P< 0.05) after the subcutaneous administration (129. ng.d/ml) compared to the intraruminal treatment (58.4. ng.d/ml). However, ivermectin concentrations measured in the gastrointestinal contents were higher in lambs treated by the intraruminal route. The mean ivermectin concentrations achieved (3. days post-treatment) in the abomasal content were 143. ng/g (intraruminal) and 2.53. ng/g (subcutaneous). Ivermectin concentrations were 15-fold higher in H. contortus recovered from intraruminally treated lambs. Whereas the subcutaneous administration reduced the number of adult nematodes from 4376 to 1300, the number of adult nematodes after the treatment with ivermectin given by the intraruminal route was 206 (P< 0.05). The higher ivermectin concentrations achieved in the digestive tract shortly after the intraruminal treatment may account for the observed enhanced efficacy compared to the parenteral administration against parasites of reduced susceptibility.